Digital Justice: Unraveling CyberLaw's Impact on Victims - Wisnu, Ido; Phahlevy, Rifqi Ridlo; Fiddina, Irta (Proceedings of The ICECRS, 2023)
In this comprehensive study, we explore the intersection of CyberLaw and victims, utilizing Lens.org database to curate a focused selection of journal articles. Our research aims to elucidate the multifaceted landscape of CyberLaw in the context of victims' rights. Employing rigorous filters for document type (journal articles) and subject (law), we meticulously analyze the selected articles. Our findings illuminate the evolving legal frameworks surrounding cybercrimes and their consequences for victims. We identify key challenges and emerging trends, shedding light on the nuanced dynamics of CyberLaw's application in victim advocacy. Through meticulous examination, this study not only enriches our understanding of the legal complexities but also underscores the pressing need for adaptive policies. These insights have profound implications for lawmakers, legal scholars, and practitioners, offering essential guidance in shaping equitable and robust CyberLaw frameworks worldwide.Highlights : This data article offers insights into Cyber Law and Victims by analyzing 500 journal articles, highlighting key institutions, publication trends, and active research areas. Notable findings include the prominence of the University of CAMBRIDGE and Michigan State University, the peak year of article production in 2017, and the leading research domains in "Psychology" and "poison control." Researchers and scholars can utilize this dataset as a reference for future studies on Cyber Law and its impact on Victims, contributing to a deeper understanding of this critical field. Keywords: Cyber Law, Victims, Scholarly Articles, Data Analysis, Research Trends